Legal Framework for Drug Optimization in Vietnam: Aligning With International Best Practices - Nguyen, Thi Bao Anh (Medicine, Law & Society, 2025)
This study investigates legal and policy reforms to strengthen Vietnam’s drug control system through a holistic approach integrating public health, legal foundations, political will, and international cooperation. Using mixed-methods, legal analysis, literature review, and comparative case studies, it assesses Vietnam’s laws against global frameworks, identifying key areas for reform. Insights from Germany and Singapore offer practical governance models. Grounded in empirical data and legal scholarship, the study proposes context-sensitive recommendations tailored to Vietnam’s institutional landscape. It contributes to global discourse on drug policy and urges policymakers to adopt integrated, adaptive strategies that reduce harm and align with international standards.